2017
DOI: 10.1038/s41598-017-08485-x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaric acid B attenuates atopic dermatitis-like skin lesions by inhibiting interleukin-17-induced inflammation

Abstract: Pseudolaric acid B (PB), isolated from the extract of the root bark of Pseudolarix kaempferi Gordon, has been used as a traditional remedy for the treatment of skin diseases. However, the information of PB on atopic dermatitis (AD) remains largely unknown. In the present study, oral administration with PB improved the severity scores of AD-like skin lesions dose-dependently in NC/Nga mice through reducing serum IgE, pro-inflammatory cytokines, and the infiltration of inflammatory cells. In addition, PB signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…PAB, containing a compact tricyclic core molecular structure, maintains anti-inflammatory effects in many diseases, including atherosclerosis and skin lesions. 19,42 Here, we observed that PAB decreased M1-polarized macrophages in vivo and in vitro, leading to decreasing synovitis, which suggest PAB could be an potential drug applicable in relieving synovial inflammation during OA.…”
Section: Discussionmentioning
confidence: 65%
“…PAB, containing a compact tricyclic core molecular structure, maintains anti-inflammatory effects in many diseases, including atherosclerosis and skin lesions. 19,42 Here, we observed that PAB decreased M1-polarized macrophages in vivo and in vitro, leading to decreasing synovitis, which suggest PAB could be an potential drug applicable in relieving synovial inflammation during OA.…”
Section: Discussionmentioning
confidence: 65%
“…PAB as a natural compound possesses excellent anti-inflammatory activity. It has been proved by previous studies, which showed that PAB ameliorated the severity of dermatitis by reducing proinflammatory cytokines and immune cell infiltration . The treatment with PAB could markedly suppress the expression of inflammatory cytokines (TNF-α, iNOS) and chemokines (MIP-2, CCL2) induced by A.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 64 reduces hypoxia‐inducible factor 1α (HIF‐1α) protein in tumor cells, which inhibits angiogenesis by diminishing the secretion of vascular endothelial growth factor (VEGF) [69] . Recently, (−)‐pseudolaric acid B has also been shown to attenuate atopic dermatitis‐like skin lesions by inhibiting interleukin‐17‐induced inflammation in NC/Nga mice [70] …”
Section: (−)‐Pseudolaric Acid Bmentioning
confidence: 99%